Tuning the electronic and magnetic properties of penta-graphene using a hydrogen atom: a theoretical study. Issue 64 (16th August 2017) - Liu, Lin-Lin; Wang, Ying; Chen, Chun-Ping; Yu, Hong-Xia; Zhao, Lu-Si; Wang, Xiao-Chun
Abstract : Through changing the adsorption configuration of the hydrogen atom, we can remarkably increase the magnetic moment of penta-graphene by 137 times. Abstract : Herein, an isolated hydrogen atom absorbed on penta-graphene (PG) was predicted to induce magnetic moments and tune the electronic properties of penta-graphene and was systematically studied using first-principles calculations. The adsorption energy and formation energy calculations suggest that magnetic penta-graphene (M-PG) and weak magnetic penta-graphene (WM-PG) of hydrogen-absorbed PG systems are energetically the most favorable states among the possible hydrogen-absorbed configurations. The hydrogen atom adsorbed on the PG sheet can effectively tune the electronic properties of PG and change it from a semiconductor to half-metallic. In the M-PG system, this spin-polarized state is essentially localized on the three-fold coordinated C atoms in the first layer opposite to that where the hydrogen atom is chemisorbed. Through changing the bond angle and bond length of the adsorbed hydrogen atom on the PG system, we can remarkably increase the magnetic moment of the hydrogen-absorbed PG system by 137 times. This would allow us to design a magnetic nanoswitch to manipulate the magnetic state of PG. We also obtained the scanning tunneling microscopy (STM) images for future experimental identification. Our findings show that the hydrogen atom absorbed on the PG system will have exciting applications in magnetic storage technology and next-generation electronic and spintronic nanodevices.